Quinazolin-4-one Coupled with Pyrrolidin-2-iminium Alkaloids from Marine-Derived Fungus Penicillium aurantiogriseum - Huanqin Dai; Hua Bai; Jidong Wang; Mei Liu; Yaojun Tong; Xueting Liu; Hong Gao; Na Yang; Hui Guo; Ke Yu; Caixia Chen; Fuhang Song; et al. (Marine Drugs, 2012)
Three new alkaloids, including auranomides A and B (1 and 2), a new scaffold containing quinazolin-4-one substituted with a pyrrolidin-2-iminium moiety, and auranomide C (3), as well as two known metabolites auranthine (4) and aurantiomides C (5) were isolated from the marine-derived fungus Penicillium aurantiogriseum. The chemical structures of compounds 1–3 were elucidated by extensive spectroscopic methods, including IR, HRESIMS and 2D NMR spectroscopic analysis. The absolute configurations of compounds 1–3 were suggested from the perspective of a plausible biosynthesis pathway. Compounds 1–3 were subjected to antitumor and antimicrobial screening models. Auranomides A–C exhibited moderate cytotoxic activity against human tumor cells. Auranomides B was the most potent among them with an IC50 value of 0.097 μmol/mL against HEPG2 cells.